2016
DOI: 10.1039/c5ob02416a
|View full text |Cite
|
Sign up to set email alerts
|

Marine AChE inhibitors isolated from Geodia barretti: natural compounds and their synthetic analogs

Abstract: Barettin, 8,9-dihydrobarettin, bromoconicamin and a novel brominated marine indole were isolated from the boreal sponge Geodia barretti collected off the Norwegian coast. The compounds were evaluated as inhibitors of electric eel acetylcholinesterase. Barettin and 8,9-dihydrobarettin displayed significant inhibition of the enzyme, with inhibition constants (Ki) of 29 and 19 μM respectively towards acetylcholinesterase via a reversible noncompetitive mechanism. These activities are comparable to those of severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 78 publications
1
60
0
Order By: Relevance
“…Given the importance of tryptamines, this class of compounds has been a frequent target for practical demonstrations of synthetic methodology, many of which begin with a substituted indole as the starting material. Classic synthetic approaches include reductive alkylation or, more recently, C−H activation . Although these traditional routes have proven quite successful, it is also desirable to develop enzymatic approaches, as they often better conform to the principles of green chemistry and have the potential to be coupled with cellular metabolism .…”
Section: Methodsmentioning
confidence: 99%
“…Given the importance of tryptamines, this class of compounds has been a frequent target for practical demonstrations of synthetic methodology, many of which begin with a substituted indole as the starting material. Classic synthetic approaches include reductive alkylation or, more recently, C−H activation . Although these traditional routes have proven quite successful, it is also desirable to develop enzymatic approaches, as they often better conform to the principles of green chemistry and have the potential to be coupled with cellular metabolism .…”
Section: Methodsmentioning
confidence: 99%
“…Cholinesterase activities were measured by the Ellman method adapted for microtiter plates, as described by Olsen et al . Stock solutions of the synthetic ruthenium compounds (1 mg mL −1 ) or neostigmine bromide, physostigmine iodide, and propidium iodide (all Sigma–Aldrich, USA) as positive controls, were prepared in 100 % EtOH and progressively diluted in 100 m m potassium phosphate buffer (pH 7.4) to a final volume of 50 μL.…”
Section: Methodsmentioning
confidence: 99%
“…Cholinesterase activities were measured by the Ellman method adapted for microtiter plates, as described by Olsen et al [57] Stock solutions of the synthetic ruthenium compounds (1 mg mL À1 ) or neostigmine bromide, physostigmine iodide, and propidium iodide ChemMedChem 2018ChemMedChem , 13, 2166ChemMedChem -2176 www.chemmedchem.org (all Sigma-Aldrich, USA) as positive controls, were prepared in 100 % EtOH and progressively diluted in 100 mm potassium phosphate buffer (pH 7.4) to a final volume of 50 mL. Then, 1 mm acetylthiocholine chloride and 0.5 mm 5,5'-dithiobis-2-nitrobenzoic acid were dissolved in the same buffer and added to the wells of the microtiter plates to the final volume of 150 mL.…”
Section: Cholinesterase Inhibition Assaymentioning
confidence: 99%
“…From the structure–activity investigation, it was shown that the brominated indole motif is not sufficient to generate a high acetylcholinesterase inhibitory activity, even when combined with natural cationic ligands for the acetylcholinesterase active site. The four natural compounds were also analysed for butyrylcholinesterase inhibitory activity and shown to display comparable activities [105]. …”
Section: Spongesmentioning
confidence: 99%